Sources of Conventional and Guerrilla Strategies in Ethno-Territorial Civil Wars - Horowitz, Shale Asher (Terrorism and political violence, 2023)
In ethno-territorial civil wars, which factors influence whether rebels choose and retain conventional warfare as their primary military strategy throughout the conflict, or whether they use guerrilla warfare as a primary strategy during periods judged to be less advantageous to conventional warfare? The existing literature almost exclusively emphasizes relative power as the determining factor: rebels use guerrilla warfare because they typically lack the capability to fight conventional wars effectively against states. I find some support for this hypothesis: ethno-territorial rebels are much more likely to fight exclusively conventional wars when external states intervene conventionally on the rebel side. I also find that rebel leaders with more intense, far-reaching nationalist goals are more likely to employ guerrilla warfare as a primary war strategy. For such leaders, the higher costs of using guerrilla methods pending an eventual transition to conventional warfare are made more acceptable by a higher valuation of the far-reaching gains delivered by military victory—gains expected to be made more likely by interim periods in which guerrilla warfare is the primary strategy. Turning to other factors, I do not find that status quo conditions or a high level of state democracy have a significant influence.